Peran Teknologi Dalam Pembelajaran Di Masa Pandemi Covid-19 - Unik Hanifah Salsabila; Lailli Irna Sari; Khusna Haibati Lathif; Ayu Puji Lestari; Asyharinur Ayuning (LPPM STAI Diniyah Pekanbaru, 2020)
The Covid-19 pandemic has caused major changes in almost all aspects of life, one of which is the education system. Changes in the education system make it difficult for students to receive the material, especially students at the Elementary School and Kindergarten levels, because learning that is usually done conventionally turns into distance-learning or done online, the implementation of which cannot be separated from the use of technology information. This journal aims to examine the role of technology in the implementation of learning during the Covid-19 pandemic, besides that it also examines the challenges of education during the Covid-19 pandemic using descriptive-analytical literature methods. The results and conclusions in this paper show that technology has an important role in the implementation of learning, especially during the Covid-19 pandemic like today. Technology plays a role as a medium in making interactions between educators and students in the implementation of online learning. In addition, technology also plays a role in facilitating educators to deliver learning material so that learning continues even though it is not done face to face. In the implementation of online learning, of course, there are obstacles that become challenges for educations actors, related to academic culture, including values, attitudes, knowledge, skills, and readiness of technology-related facilities and infrastructure. The implementation of literacy and training related to the use of technology can be a solution to facing some of the challenges of online learning during the current Covid-19 pandemic.